1995
DOI: 10.1007/bf02635652
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative extraction of pecan oil from small samples with supercritical carbon dioxide

Abstract: A procedure to determine total oil content of pecan was developed for samples weighing 500 and 10 mg by supercritica[ fluid extraction (SFE) with carbon dioxide as the extraction solvent, and chilled hexane as the trapping solvent. Fatty acid methyl esters (FAMEs) were prepared from the total lipid fraction by using either an aliquot (500 mg starting weight) or the entire extract (10 mg starting weight). Total oil content obtained for either sample size with SFE was similar to that obtained with an organic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
7
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 9 publications
6
7
0
Order By: Relevance
“…King et al (56) concluded that there were no significant differences between fatty acids extracted with an SFE method and with the solvent extraction step of the NLEA procedure in beef samples. Berg et al (57) showed that results for total fat and several lipid classes in meat coincided with those from the Bligh and Dyer procedure (10), and yields reported by Maness et al (58) and Melinz et al (59) seem to be similar to those obtained with conventional methods. Likewise, fatty acid contents determined by an SFE method and by an acid hydrolysis solvent extraction procedure were comparable in beef and bakery samples (60).…”
supporting
confidence: 68%
“…King et al (56) concluded that there were no significant differences between fatty acids extracted with an SFE method and with the solvent extraction step of the NLEA procedure in beef samples. Berg et al (57) showed that results for total fat and several lipid classes in meat coincided with those from the Bligh and Dyer procedure (10), and yields reported by Maness et al (58) and Melinz et al (59) seem to be similar to those obtained with conventional methods. Likewise, fatty acid contents determined by an SFE method and by an acid hydrolysis solvent extraction procedure were comparable in beef and bakery samples (60).…”
supporting
confidence: 68%
“…Some differences were comparable to the variability of the method. These results confirmed the findings of King et al (1996) and Maness et al (1995).…”
Section: Fatty Acid Analysis Of Fat Extracted By Sfesupporting
confidence: 91%
“…King et al (1996) demonstrated that fatty acid composition after SFE was similar to that of the fat obtained by solvent extraction. The same result has been shown by Maness et al (1995).…”
supporting
confidence: 86%
“…King et al (1996) concluded that there were no significant differences between fatty acids extracted with an SFE method and with the solvent extraction step of the nutritional labelling and education act (NLEA) procedure in beef samples. Berg et al (1997) showed that results for total fat and several lipid classes in meat coincided with those from the Bligh and Dyer procedure (1959), and yields reported by Maness et al (1995) and Melinz et al (1997) were similar to those obtained with conventional methods. Likewise, fatty acid contents determined by an SFE method and by an acid hydrolysis solvent extraction procedure were comparable in beef and bakery samples (Eller and King, 1998).…”
Section: Comparison Of Sc-co 2 and Solvent Extractionsupporting
confidence: 73%